An Analysis of Feminist Criticism in The Lyrics of “The Man” Song by Taylor Swift - Amanda, Vina; Gumelar, Rizdki Elang; Riandi, Riandi (Universitas Mathla'ul Anwar Banten, 2024)
This research paper aims to find out the kinds of feminism and analyze the literal meaning of